STUDI KEGAGALAN BANK DI INDONESIA - Ahmad Fuad, - (2021)
This dissertation is a research on bank failures in Indonesia. Bank failure is interesting to study considering the number of failed banks (no longer operating) since 1995 - 2018 reached 125 banks and the impact of bank failures has a major impact on the economy of a country. The purpose of this study is first to develop a prediction model for the probability of bank failure in Indonesia by examining the effect of bank liquidity management through capital processes on the probability of bank failure. Second, including the level of bank competition as a moderating variable (strengthening or weakening) on the effect of liquidity management on the probability of bank failure mediated by bank capital. The researcher also included six control variables from internal and external factors of the bank. The sample data used is 96 conventional commercial banks in Indonesia for the period 2008 - 2018 with the sampling technique is purposive sampling. The total number of data observed was 1,056 during the study period. The data analysis used panel data regression analysis with the Hayes model 59 method. The findings of the study show that bank competition weakens the effect of liquidity creation on the probability of bank failure through capital mediators at the level of α = 0.05. This means that the risk of bank failure caused by liquidity through the capital process depends on competition. The second finding is that competition plays a role in weakening the inverse effect of liquidity creation on bank capital at the level of α = 0.05. Third, competition plays a role in strengthening the inverse effect of liquidity creation on the probability of bank failure at the level of α = 0.10. The four competitions play a role in strengthening the inverse effect of capital on the probability of bank failure at the level α = 0.10. The implication of this research result is that banks need to be aware of the impact of decreasing bank liquidity due to increased liquidity creation by maintaining a balance of assets and liabilities. In addition, the sensitivity of regulators in determining the minimum capital obligation needs to take into account competition factors.